2021
DOI: 10.4018/ijhisi.20211001.oa15
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Adoption Intention of Blockchain and Internet-of-Things Technologies for Sustainable Blood Bank Management

Abstract: Owing chiefly to the lack of suitable technology solutions, India is experiencing both shortage and wastage of blood units. In addressing such a challenge, we explore the unique role of Blockchain and Internet-of-things technologies in the overall blood supply chain management as an appropriate technology solution. Our study employs an integrated Task-Technology Fit and Technology Acceptance Model to empirically test and identify key factors influencing the adoption intention of the Blockchain and Internet-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 96 publications
(158 reference statements)
5
24
1
Order By: Relevance
“…Moreover, users interacting with chatbots often report high failure rates and levels of scepticism, suggesting that more research is needed on how to design and introduce chatbots to users (Araujo, 2018). This observation is in line with the notion that chatbot research is currently inclined toward technical aspects with only a few studies focussing on the social dimensions, such as technology adoption (Kuberkar & Singhal, 2020). Furthermore, there is very little research on chatbots’ acceptability and motivation for use in the helping professions in general (Nadarzynski et al, 2019).…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…Moreover, users interacting with chatbots often report high failure rates and levels of scepticism, suggesting that more research is needed on how to design and introduce chatbots to users (Araujo, 2018). This observation is in line with the notion that chatbot research is currently inclined toward technical aspects with only a few studies focussing on the social dimensions, such as technology adoption (Kuberkar & Singhal, 2020). Furthermore, there is very little research on chatbots’ acceptability and motivation for use in the helping professions in general (Nadarzynski et al, 2019).…”
Section: Introductionsupporting
confidence: 84%
“…Davis et al (1989) found that people are more likely to use an application if they perceive it as easy to use. In previous studies, a positive relationship between effort expectancy and behavioral intent was found in web-based learning (Chiu & Wang, 2008), mobile banking (Shan & Lu, 2009), health information technology (Kijsanayotin et al, 2009), and as well as with service-oriented chatbots (Kuberkar & Singhal, 2020).…”
Section: Hypothesesmentioning
confidence: 92%
See 2 more Smart Citations
“…Boosting the efficiency and productivity in the engineering field with the implication of automation considering AI technology is the most common way to leverage artificial intelligence. AI powered chat bots are another way to gather artificial knowledge regarding communication skills development [16]. Understanding the insights of project operations using artificial intelligence has helped to make decisions in the favour of the project in the engineering field.…”
Section: Way Of Leveraging Artificial Intelligencementioning
confidence: 99%